Impact of Value Management on Building Projects Success: Structural Equation Modeling Approach - Kineber, A.F. (American Society of Civil Engineers (ASCE), 2021)
In the last two decades, value management (VM) has become an established construction practice based on fundamental approaches. Implementation of VM activities can contribute to enhancement of the initial objectives in terms of cost, quality, and time. However, the VM activities adopt informal approaches in the Egyptian construction industry. This study aims to develop a VM implementation model by investigating the relationship between VM implementation and the overall project success (OPS) in Egyptian building projects. Fifteen experts were interviewed to assess the VM activities obtained from previous studies. Exploratory factor analysis (EFA) was used to validate the results from the interviews. Structured questionnaires completed by building professionals were further employed to investigate the importance of these VM activities. Partial least squared structural equation modeling (PLS-SEM) was used to determine and confirm the factors structure and examine the relationships between the VM implementation and OPS. The results showed a moderate association, with the implementation of the VM contributing 55.5 to the success of the project. The findings can be used as a benchmark for decision-makers to minimize costs and boost efficiency by implementing VM in the Egyptian construction industry. This study advances the current construction engineering management by improving the understanding of VM methods and activities. Â© 2021 American Society of Civil Engineers.